Some Common Fixed Point Theorems in Complex Valued Metric Spaces: Ebrahim Analouei Adegani, Ahmad Motamednezad - Team, Support (Thai Journal of Mathematics, 2022)
In this work, some common fixedpoint results for the mappings satisfying rational expressions on aclosed ball in complex valued metric spaces will be proposed.Presented theorems can be realized as extensions of some well-knownresults in the literature. Further, our result is well supported bynontrivial example which shows that the improvement is a actual.